The contribution of community governance towards the sustainable planning and management of urban and regional green infrastructure - George, Jennifer (Curtin University, 2018)
This study explored the contribution of community governance towards the sustainable planning and management of urban green infrastructure in Australia. The three case study projects were green corridors in different states in Australia: Merri Creek in Melbourne, Victoria; Iron Cove to Cooks River GreenWay in Sydney, NSW; and the Bibbulmun Track in WA. The case studies suggested that where community and government partners have high capacity in community governance then sustainability outcomes can be achieved.